Geochemical peculiarities of black poplar leaves (Populus nigra L.) in the sites with heavy metals intensive fallouts - Yalaltdinova A. R. Albina Rashidovna; Baranovskaya N. V. Nataliya Vladimirovna; Rikhvanov L. P. Leonid Petrovich; Matveenko I. A. Irina Alekseevna (2013, 2013)
Заглавие с экрана